1990
DOI: 10.1016/0140-6736(90)91528-i
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous abortion rate and advanced maternal age: consequences for prenatal diagnosis

Abstract: Maternal age related and procedure-related fetal abortion rates were studied in 384 women aged 36 and over scheduled for transabdominal chorionic villus sampling (TA-CVS) at 12-14 weeks of gestation. The pre-TA-CVS abortion rate within 30 days of intake (at 6-10 weeks of gestation) rose from 1.9% at age 35-36 years to 10.9% at 40 years and older. Women entering in the 6th week of gestation had a greater probability of aborting before TA-CVS than women entering after day 48. 26 women aborted spontaneously befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
3

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 13 publications
3
13
1
3
Order By: Relevance
“…A study that diagnosed pregnancy with daily urine specimens estimated a rate of 22 per cent for early spontaneous abortions that would not normally be noticed and a total rate of 31 per cent, including those happening later in pregnancy [69]. Most studies of spontaneous abortion start from the point where the mother is clearly known to be pregnant; they indicate a rate of 1-2% in young women rising to 7-10% in women over 35 [70,71]. In a study of 31-36 year-old Australian women, the total rate of spontaneous abortion was 25 per cent [72].…”
Section: The Range Of Issues (A) Medically Significant Genetic Variationmentioning
confidence: 99%
“…A study that diagnosed pregnancy with daily urine specimens estimated a rate of 22 per cent for early spontaneous abortions that would not normally be noticed and a total rate of 31 per cent, including those happening later in pregnancy [69]. Most studies of spontaneous abortion start from the point where the mother is clearly known to be pregnant; they indicate a rate of 1-2% in young women rising to 7-10% in women over 35 [70,71]. In a study of 31-36 year-old Australian women, the total rate of spontaneous abortion was 25 per cent [72].…”
Section: The Range Of Issues (A) Medically Significant Genetic Variationmentioning
confidence: 99%
“…Fetal bradycardia and fetal tachycardia are associated with a high rate of miscarriage [24]. Yagel et al [9] demonstrated better correlation between FHR and CRL rather than gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, este percentual não tem sido confirmado por outros autores 4,9,13 , inclusive por este trabalho. Everett 4 refere que mulheres com antecedente de abortamento não apresentam um risco significativamente maior de uma segunda perda fetal consecutiva.…”
Section: Abortamentounclassified